New experimental measurements of the H2-CO2 Collision-Induced Absorption in the [3907, 4770] cm−1 spectral range from 241 to 498 K - F. Vitali; S. Stefani; G. Piccioni; H. Tran; M. Snels; D. Grassi; C. Boulet; D. Biondi; A. Boccaccini (Icarus, 2026)

Exposure assessment to waste anesthetic isoflurane during large-animal surgery: Environmental, personal and biological monitoring - Mariana G. Braz; Tony F. Grassi; Maria Vitória Destro; Francisco J. Teixeira-Neto; Leandro G. Braz (Environmental Toxicology and Pharmacology, 2026)

Evaluation of genetic instability in patients with amyotrophic lateral sclerosis - Hendrew J.B.C. Souza; Kátina M. Souza; Matheus B. dos Santos; Mariane A.P. Silva; Tony F. Grassi; Maria V. Destro; Mariana G. Braz (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

A simulator of the MAJIS instrument onboard the JUICE mission: Description and application to operational and scientific cases - C. Royer; P. Haffoud; Y. Langevin; F. Poulet; D. Bockelée-Morvan; E. D’Aversa; M. Cisneros-González; D. Grassi; N. Ligier; G. Piccioni; J. Carter; F. Tosi; et al. (Planetary and Space Science, 2025)

Environmental and biological measurements of the anesthetic isoflurane and its possible toxic effects in veterinarians - Tony F. Grassi; Mariane A.P. Silva; Maria V. Destro; Bruno S. De Martinis; Leandro G. Braz; Mariana G. Braz (Environmental Toxicology and Pharmacology, 2025)

Deformed archaeological remains at Lilybaeum in Western Sicily (southern Italy): possible ground signatures of a missed large earthquake - G. Barreca; F. Pepe; A. Sulli; G. Morreale; S. Gambino; M. Gasparo Morticelli; S. Grassi; C. Monaco; S. Imposa (Natural Hazards, 2025)
Archaeoseismic analysis performed in Western Sicily points to deformed archeological remains at Lilybaeum , a Punic coastal city founded in 397 B.C. at the Island’s westernmost edge. Starting from the direct observation of deformed ruins, an interdisciplinary work strategy, which included field-structural analysis, drone-shot high-resolution aerial photogrammetry, and geophysical prospecting, was employed to investigate whether the identified deformations may represent the ground effects of a previously unknown large earthquake in the area. Among the unearthed remains, some mosaics and a stone-paved monumental avenue show evidence of tectonic deformation, being fractured, folded, and uplifted. The trend of folding and fracturing is consistent with the NNW–SSE oriented tectonic max stress axis to which Western Sicily is currently subjected. Displacement along a fracture deforming the Decumanus Maximus together with the finding of a domino-type directional collapse, enable us to interpret the observed deformation as the ground signature of a coseismic slip. The seismic rupture occurred along a previously unmapped deformation front that fits well within the seismotectonic context of Western Sicily. Measured offset, geophysical prospecting, and age-constraints all suggest the possibility that a highly-energetic earthquake nucleated in the area following a coseismic rupture along a NE–SW trending back-verging reverse fault towards the end of the fourth century CE. Since seismic catalogs do not provide evidence of such a large earthquake, this event might represent a missed entry in the historical seismic record. This finding provides constraints to redefine the seismic hazard of Western Sicily, a region where recurrence-time intervals for large earthquakes are still unknown.

nano-TiO2 reduces bioavailability and biotransformation responses to crude oil WAF-associated PAHs in the European sea bass Dicentrachus labrax - M.L. Vannuccini; C. Della Torre; G. Grassi; C. Zambonin; P. Cotugno; M.J. Leaver; I. Corsi (Marine Pollution Bulletin, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A quick combined approach for the characterization of a cliff during a post-rockfall emergency - G. Pappalardo; S. Mineo; S. Imposa; S. Grassi; A. Leotta; F. La Rosa; D. Salerno (Landslides, 2020)

Potential of Cedrella fissilis bark as an adsorbent for the removal of red 97 dye from aqueous effluents - Jordana Georgin; Dison S. P. Franco; Patricia Grassi; Denise Tonato; Daniel G. A. Piccilli; Lucas Meili; Guilherme L. Dotto (Environmental Science and Pollution Research, 2019)

Study of landslides at the archaeological site of Abakainon necropolis (NE Sicily) by geomorphological and geophysical investigations - G. Pappalardo; S. Imposa; M. S. Barbano; S. Grassi; S. Mineo (Landslides, 2018)

Association Between the Serum Uric Acid Levels and Lacunar Infarcts in the Elderly - F. Crosta; U. Occhiuzzi; G. Passalacqua; E. Occhiuzzi; A. Cimini; D. Grassi; C. Ferri; C. Marini; C. Borghi; G. Desideri (Journal of Molecular Neuroscience, 2018)

Geophysical surveys to study a landslide body (north-eastern Sicily) - S. Imposa; S. Grassi; F. Fazio; G. Rannisi; P. Cino (Natural Hazards, 2017)

3D Subsoil Model of the San Biagio ‘Salinelle’ Mud Volcanoes (Belpasso, Sicily) derived from Geophysical Surveys - S. Imposa; S. Grassi; G. De Guidi; F. Battaglia; G. Lanaia; S. Scudero (Surveys in Geophysics, 2016)

Behavior of Atrazine and Its Degradation Products Deethylatrazine and Deisopropylatrazine in Oxisol Samples - Maristela F. Amadori; Marcio B. Rodrigues; Caio C. Rebouças; Patricio G. Peralta-Zamora; Marco T. Grassi; Gilberto Abate (Water, Air, & Soil Pollution, 2016)

Drosophila suzukii population response to environment and management strategies - Nik G. Wiman; Daniel T. Dalton; Gianfranco Anfora; Antonio Biondi; Joanna C. Chiu; Kent M. Daane; Beverly Gerdeman; Angela Gottardello; Kelly A. Hamby; Rufus Isaacs; Alberto Grassi; Claudio Ioriatti; et al. (Journal of Pest Science, 2016)

Gokyo Khumbu/Ama Dablam Trek 2012: effects of physical training and high-altitude exposure on oxidative metabolism, muscle composition, and metabolic cost of walking in women - E. Tam; P. Bruseghini; E. Calabria; L. Dal Sacco; C. Doria; B. Grassi; T. Pietrangelo; S. Pogliaghi; C. Reggiani; D. Salvadego; F. Schena; L. Toniolo; et al. (European Journal of Applied Physiology, 2016)

Tracking the invasion of the alien fruit pest Drosophila suzukii in Europe - A. Cini; G. Anfora; L. A. Escudero-Colomar; A. Grassi; U. Santosuosso; G. Seljak; A. Papini (Journal of Pest Science, 2014)

Assessment of sweet potato [ Ipomoea batatas (L.) Lam] for bioethanol production in southern Italy - A. Montefusco; M. Durante; S. Grassi; G. Piro; G. Dalessandro; M. S. Lenucci (Plant Biosystems, 2014)

The role of the land use, land use change and forestry sector in achieving Annex I reduction pledges - Giacomo Grassi; Michel G. J. den Elzen; Andries F. Hof; Roberto Pilli; Sandro Federici (Climatic Change, 2012)

Genetic diversity in the endangered Sicilian endemic Brassica rupestris : Proposals for a conservation strategy - F. M. Raimondo; A. Scialabba; G. Zecca; F. Grassi; G. Casazza; L. Minuto (Plant Biosystems, 2012)

Efficient automatic classifiers for the detection of A phases of the cyclic alternating pattern in sleep - Sara Mariani; Elena Manfredini; Valentina Rosso; Andrea Grassi; Martin O. Mendez; Alfonso Alba; Matteo Matteucci; Liborio Parrino; Mario G. Terzano; Sergio Cerutti; Anna M. Bianchi (Medical & Biological Engineering & Computing, 2012)

Sequence analysis of human rotavirus strains: comparison of clinical isolates from Northern and Southern Italy - T. Grassi; F. Bagordo; A. Cavallaro; M. Guido; C. Malaventura; G. Gabutti; A. Donno (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Allopatric divergence and secondary contacts in Euphorbia spinosa L: Influence of climatic changes on the split of the species - G. Zecca; G. Casazza; L. Minuto; M. Labra; F. Grassi (Organisms Diversity & Evolution, 2011)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)
Overviewing the European carbon (C), greenhouse gas (GHG), and non‐GHG fluxes, gross primary productivity (GPP) is about 9.3 Pg yr −1 , and fossil fuel imports are 1.6 Pg yr −1 . GPP is about 1.25% of solar radiation, containing about 360 × 10 18 J energy – five times the energy content of annual fossil fuel use. Net primary production (NPP) is 50%, terrestrial net biome productivity, NBP, 3%, and the net GHG balance, NGB, 0.3% of GPP. Human harvest uses 20% of NPP or 10% of GPP, or alternatively 1‰ of solar radiation after accounting for the inherent cost of agriculture and forestry, for production of pesticides and fertilizer, the return of organic fertilizer, and for the C equivalent cost of GHG emissions. C equivalents are defined on a global warming potential with a 100‐year time horizon. The equivalent of about 2.4% of the mineral fertilizer input is emitted as N 2 O. Agricultural emissions to the atmosphere are about 40% of total methane, 60% of total NO‐N, 70% of total N 2 O‐N, and 95% of total NH 3 ‐N emissions of Europe. European soils are a net C sink (114 Tg yr −1 ), but considering the emissions of GHGs, soils are a source of about 26 Tg CO 2 C‐equivalent yr −1 . Forest, grassland and sediment C sinks are offset by GHG emissions from croplands, peatlands and inland waters. Non‐GHGs (NH 3 , NO x ) interact significantly with the GHG and the C cycle through ammonium nitrate aerosols and dry deposition. Wet deposition of nitrogen (N) supports about 50% of forest timber growth. Land use change is regionally important. The absolute flux values total about 50 Tg C yr −1 . Nevertheless, for the European trace‐gas balance, land‐use intensity is more important than land‐use change. This study shows that emissions of GHGs and non‐GHGs significantly distort the C cycle and eliminate apparent C sinks.

Haplotype richness in refugial areas: phylogeographical structure of Saxifraga callosa - F. Grassi; L. Minuto; G. Casazza; M. Labra; F. Sala (Journal of Plant Research, 2009)

Ecogeographic and genetic evaluation of endemic species in the Maritime Alps: the case of Moehringia lebrunii and M. sedoides (Caryophyllaceae) - L. Minuto; F. Grassi; G. Casazza (Plant Biosystems, 2006)

Comparison between recombinant baculo- and adenoviral-vectors as transfer system in cardiovascular cells - G. Grassi; H. Köhn; B. Dapas; R. Farra; J. Platz; S. Engel; S. Cjsareck; R. Kandolf; C. Teutsch; R. Klima; G. Triolo; A. Kuhn (Archives of Virology, 2006)

Special Contribution: An Overview of Recent Seismic Refraction Experiments in Central Europe - A. Guterch; M. Grad; A. Špičák; E. Brückl; E. Hegedüs; G.R. Keller; H. Thybo; K. Aric; S. Acevedo; I. Asudeh; M. Behm; A. A. Belinsky; et al. (Studia Geophysica et Geodaetica, 2003)

Structure-effect relationships of amiodarone analogues on the inhibition of thyroxine deiodination - H. R. Ha; B. Stieger; G. Grassi; H. R. Altorfer; F. Follath (European Journal of Clinical Pharmacology, 2000)

Effect of different combinations of sparfloxacin, oxacillin, and fosfomycin against methicillin-resistant staphylococci - A. Ferrara; C. Dos Santos; M. Cimbro; G. Gialdroni Grassi (European Journal of Clinical Microbiology & Infectious Diseases, 1997)